African People, Education for Liberation & Staying Human: Reflections on Walter Rodney and the Pan-African / Black Liberation Tradition. (1st July 2018) - King, Joyce E.
Abstract : On March 25 th, 2017, Dr. Joyce E. King delivered this talk as the day two keynote of the 14 th Annual Walter Rodney Symposium at the Atlanta University Center Robert W. Woodruff Library, Atlanta, Georgia.